Serglycin’s role in primary liver cancer: insights into tumor microenvironment and macrophage interaction - Lian, Qinghai; Ma, Chonghan; Wang, Xiaoxiao; Wang, Jiani; Zeng, Jindi; Zhang, Jiongshan; Li, Yongwei (Frontiers in Immunology, 2025)
BackgroundSerglycin (SRGN) is an important proteoglycan that regulates tumorigenesis, but its role in primary liver cancer (PLC) remains unclear.MethodsWe investigated the expression and prognostic potential of SRGN in PLC using bioinformatics analyses. HepG2 cells were transfected with an SRGN over expression vector and their proliferation, migration, invasion, resistance to sorafenib, and angiogenic capacity were examined in vitro. A subcutaneous xenograft tumor model was created using nude mice. SRGN overexpressing hepatoma cells were co-cultured with THP-1 derived macrophages. The expressions of CD80 and CD206, secretory molecules, and the NF-κB and STAT3 signal pathways were examined by flow cytometry, ELISA and western blot, respectively. Transwell migration and invasion were investigated in HepG2 and Huh7 co-cultured with SRGN-promoted macrophages.ResultsSingle-cell analysis revealed SRGN expression across 17 distinct cell subpopulations, with higher expression in macrophages in tumor tissues compared to those in normal tissues. SRGN displayed consistent high expression across cell cycle phases while exhibited dynamic expression during macrophage pseudotime trajectory. Cell communication analysis indicated that SRGN was involved in interactions within the tumor microenvironment (TME), particularly in the VEGF signaling network. Autocrine SRGN promoted in vitro aggressiveness, especially pro-angiogenic activity, and in vivo tumorigenicity of HepG2 cells, and conferred resistance to sorafenib. Paracrine SRGN promoted a partial polarization of TAMs toward an M2-like phenotype, accompanied by the activation of signaling pathways including NF-κB and STAT3. Levels of secreted argase1 and SRGN were increased in the supernatant. The invasion and migration of hepatoma cells were promoted by SRGN-overexpressing TAMs.ConclusionsOur findings highlight the role of SRGN in the TME of PLC. SRGN-high TAMs are induced by paracrine SRGN from hepatoma cells, establishing a self-reinforcing mechanism that drives PLC progression. Therapeutic strategies targeting SRGN should take into account its context-specific roles depending on TME cells.